2014
DOI: 10.1158/1535-7163.mct-14-0324
|View full text |Cite
|
Sign up to set email alerts
|

Withanone-Rich Combination of Ashwagandha Withanolides Restricts Metastasis and Angiogenesis through hnRNP-K

Abstract: Ashwagandha is an important herb used in the Indian system of traditional home medicine, Ayurveda. Alcoholic extract (i-Extract) from its leaves and its component, withanone, were previously shown to possess anticancer activity. In the present study, we developed a combination of withanone and withaferin A, major withanolides in the i-Extract, that retained the selective cancer cell killing activity and found that it also has significant antimigratory, -invasive, and -angiogenic activities, in both in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 46 publications
2
68
0
Order By: Relevance
“…VEGF expression was significantly reduced in ASH-WEX-fed rats as compared to PBS-fed animals. This is in line with previous studies which have shown ashwagandha to inhibit VEGF expression leading to restricted angiogenesis [41,42]. Taken together, these results strongly support that ASH-WEX has the potential to block in vivo invasion of gliomas and angiogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…VEGF expression was significantly reduced in ASH-WEX-fed rats as compared to PBS-fed animals. This is in line with previous studies which have shown ashwagandha to inhibit VEGF expression leading to restricted angiogenesis [41,42]. Taken together, these results strongly support that ASH-WEX has the potential to block in vivo invasion of gliomas and angiogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…An alternative mechanism of action of withaferin A, obtained from Withania somnifera, was also presented by another study, where withaferin A was shown to inhibit NF-kB activity in HUVEC cells [165]. Additionally, Gao et al [166], studied the combination of withanone and withaferin A, verifying that this combination showed significant antimigratory and antiangiogenic activities, both in vitro or in vivo assays. Furthermore, the authors demonstrated, by using bioinformatic and biochemical approaches, that withanone and withaferin A caused downregulation of VEGF and MMPs.…”
Section: Antiangiogenic Potential Of Other Natural Compoundsmentioning
confidence: 84%
“…It was shown to cause selective cytotoxicity on cancer cells by irreversibly damaging DNA repair mechanisms, disturbing the cellular assembly and organization, and mortalin-p53 function [18,19,24]. Several studies have suggested anti-inflammatory and anti-stress potential of Wi-N [38,39]; they have attributed this property to the oxidized 5-7 carbons in its chemistry [40] that translates into weak binding affinity to target proteins [19].…”
Section: Discussionmentioning
confidence: 99%
“…We have earlier demonstrated that ashwagandha (Indian ginseng)-derived withanolides possess significant anticancer activity in in vitro and in vivo [18][19][20][21][22][23][24][25] [26,27]. Molecular studies have demonstrated activation of tumor suppressor function, oxidative and DNA damage selectively in cancer cells [21,24].…”
Section: Introductionmentioning
confidence: 99%